Endometriosis: From diagnosis to treatment of the most prevalent female disease in society (Research, Society and Development, 2024)
Endometriosis is a gynecological condition of unknown etiology that affects the quality of life of many women. It is defined by the presence of tissue similar to the endometrium in places outside the uterine cavity, mainly in the pelvis. To prepare the work, an integrative literature review was carried out with searches in the Pubmed, LILACS, VHL, SciELO databases and analysis of books on the topic. The following descriptors were used: endometriosis, diagnosis, treatment. The definitive diagnosis of endometriosis is mandatory through surgical intervention. Currently, videolaparoscopy with biopsy is considered the gold standard, but the symptoms and findings in physical, imaging and laboratory examinations can predict the positive picture of the disease with a high degree of diagnostic certainty. Endometriosis treatment must be carried out individually according to the needs of each patient, and can be medication, surgery or a combination of both methods. The aim of this review is to provide a broad approach to endometriosis, a gynecological disease that affects millions of women of reproductive age and is an important cause of impaired quality of life and female infertility.